2008
DOI: 10.1007/s00454-008-9110-x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Dimension Reduction Using Rademacher Series on Dual BCH Codes

Abstract: The Fast Johnson-Lindenstrauss Transform (FJLT) was recently discovered by Ailon and Chazelle as a novel technique for performing fast dimension reduction with small distortion fromachieved by naive multiplication by random dense matrices, an approach followed by several authors as a variant of the seminal result by Johnson and Lindenstrauss (JL) from the mid 80's. In this work we show how to significantly improve the running time, for any arbitrary small fixed δ. This beats the better of FJLT and JL. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
257
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(260 citation statements)
references
References 20 publications
3
257
0
Order By: Relevance
“…In this work we extend and simplify the result in [25]. Here we compose any column normalized fixed matrix A with a random diagonal matrix D s and give a sufficient condition on the p norm of input vectors x for which the composition AD s is a good random projection.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this work we extend and simplify the result in [25]. Here we compose any column normalized fixed matrix A with a random diagonal matrix D s and give a sufficient condition on the p norm of input vectors x for which the composition AD s is a good random projection.…”
Section: Introductionmentioning
confidence: 91%
“…This can be done using the Ailon and Liberty [25] construction serving as the random projection matrix R. R is a k ×d Johnson Lindenstrauss projection matrix which can be applied ind log(k) operations ifd = d α ≥ k 2+δ for arbitrary small δ . For the same choice of a seed as in lemma 2.2, the condition becomes d ≥ k 2+δ +2δ which can be achieved by d ≥ k 2+δ for arbitrary small δ depending on δ and δ .…”
Section: Controlling α and Choosing Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Roughly speaking, since the average number of nonzero entries of the matrix P is just O(log 2 N ), FJLT is a fast scheme because there is a significant reduction of the amount of computation of P. In [7], J. Matousek shown that it is possible to replace the Gaussian distribution N (0, q − 1) by Bernoulli (±1) distribution without incurring the dimensionality penalty, further speeding up the computation. Then, in [8], D. Ailon et al showed a simpler variant of FJLT by replacing a sparse random matrix P by a deterministic 4-wise independent code matrix (e.g. BCH codes).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we extend and simplify the result in [25]. Here we compose any column normalized fixed matrix A with a random diagonal matrix D s and give a sufficient condition on the p norm of input vectors…”
Section: Introductionmentioning
confidence: 90%